PROSPEK PELESTARIAN DAN PENGEMBANGAN BANGUNAN PESANGGRAHAN - Sambung Widodo (Berkala Arkeologi, 2003)
Seeing the fact that there are still quite a lot of pesanggrahan buildings that are still standing today even though they are not in very good condition, it is hoped that efforts can be made to prevent the decline in the quality of the archaeological resources. In addition, it is necessary to take security measures, among others, by providing awareness to the public at large, as well as in various agencies if necessary and provision of adequate funds. In order to prevent the decline in the quality of archaeological resources in the form of pesanggrahan buildings, the following points can be stated: as a first step, of course it is necessary to undertake a sufficiently complete and comprehensive inventory and research of the existing pesanggrahan buildings. Furthermore, these steps should also be followed by the issuance of heritage decree as a binding for the users or managers of these buildings.